RETRACTED ARTICLE: The impact of letrozole on oocyte quality in assisted reproductive technology (ART); a randomized double-blind clinical trial - Batool Hossein Rashidi; Ensieh Shahrokh Tehraninejad; Saeed Amanpour; Fatemeh Bandarian; Mahin Bandarian (Taylor & Francis Group, 2022)
Batool Hossein Rashidi, Ensieh Shahrokh Tehraninejad, Saeed Amanpour, Fatemeh Bandarian & Mahin Bandarian (2022) The impact of letrozole on oocyte quality in assisted reproductive technology (ART); a randomized double-blind clinical trial, Gynecological Endocrinology, 38:12, 1087-1092, DOI: http://dx.doi.org/10.1080/09513590.2022.2160869Since publication, significant concerns have been raised about the integrity of the data and reported results in the article. When approached for an explanation, the authors have not adequately addressed the concerns raised, and they have not provided their original data to verify that the research and published article comply with the journal's Editorial Policies. As verifying the validity of published work is core to the integrity of the scholarly record, we are therefore retracting the article. The authors have been informed, and they do not agree with the retraction.We have been informed in our decision-making by our editorial policies and COPE guidelines.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted.'